Paid–unpaid work continuum of women: Home-based workers and self-employed women in the national capital region - Sengupta, Sudeshna (Indian Journal of Labour Economics, 2019)
Women’s work is a continuum that intersperses productive work with reproductive work, unpaid work with paid work and all kinds of activities with leisure and self-care. She plans, manages and implements her work at home, often being responsible for all the three domains. Women from working-class families may seem to be making a “choice” in deciding the continuum, and delving deep, we find that it is more often a “coping mechanism” in “managing poverty” of all forms—income, time and opportunity. This paper explores how women’s organisation of work is influenced by the interplay of three institutions—State, market and family, and how gendered division of work is reproduced in the process. © 2019, Indian Society of Labour Economics.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asie; conciliation famille-travail; division sexuelle du travail; famille; inde; pauvreté; projet charge mentale; périodes historiques; rapports sociaux de sexe; régions géographiques; thématiques; travail; travail de reproduction; travail gratuit; travail rémunéré; travailleuses à domicile

Santé sexuelle et autonomie reproductive : étude qualitative sur les expériences et représentations des femmes universitaires de Mumbai, Inde - Beauchemin-Roy, Sarah (Université du Québec à Montréal, 2018)
Cette recherche vise à explorer les expériences et représentations des femmes indiennes universitaires quant à leur santé sexuelle et reproductive. Plus précisément, il s'agit d'explorer les normes sociales et les enjeux associés à la décision d'avoir une vie sexuelle active ; de documenter les expériences et perceptions des femmes quant à leurs connaissances et à l'utilisation des méthodes de contraception ; et de décrire leur pouvoir de décision et de contrôle sur leur stratégie contraceptive. Pour y arriver, une recherche qualitative exploratoire a été menée de septembre à novembre 2016 à Mumbai, en Inde. Les 10 participantes sont des étudiantes au collège ou à l'université, sexuellement actives dans les douze derniers mois, âgées de 20 à 25 ans, qui ont pris part à une entrevue semi-dirigée de 60 minutes. Les résultats indiquent que les jeunes femmes universitaires font face à de nombreux obstacles à l'atteinte d'une autonomie reproductive et donc, d'une santé sexuelle et reproductive optimale. Tout d'abord, les normes patriarcales établies par les structures sociales et culturelles influencent les représentations de la sexualité féminine dans la société. Ensuite, quant aux expériences sexuelles des participantes, elles sont modulées par la famille et le réseau des pairs ; le premier étant un obstacle et le deuxième étant un facilitateur à la transgression des normes et des attentes sociales envers les femmes. Enfin, plusieurs facteurs interpersonnels et individuels élaborés dans ce mémoire jouent un rôle déterminant dans l'atteinte d'une autonomie reproductive. Pour conclure, il sera pertinent de se pencher sur les limites de cette recherche ainsi que sur des recommandations. Or, considérant que des changements majeurs sont nécessaires à plusieurs niveaux, des recommandations globales seront proposées. ______________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : autonomie reproductive, santé sexuelle et reproductive, justice reproductive, méthodes contraceptives, étudiantes collégiales et universitaires, Mumbai, Inde
Keywords: 2000 à aujourd'hui; 2010-2019; IREF; asie; contraception; discipline; inde; justice reproductive; mémoires/thèses; périodes historiques; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; sexualité des femmes*; thématiques; étudiantes indiennes

The association between satisfaction with husband's participation in housework and suicidal ideation among married working women in Korea. - Lee, Sang Ah; Park, Eun-Cheol; Ju, Yeong Jun; Han, Kyu-Tae; Yoon, Hyo Jung; Kim, Tae Hyun (Psychiatry research, 2018)
Although married women are increasingly participating in paid labor, housework remains their primary responsibility. This uneven distribution of housework could have a negative impact on their mental health. In this study, we examined the association between satisfaction with husbands' participation in housework and suicidal ideation in married working women. Data were obtained from 3544 participants of the fourth and fifth waves of the Korean Longitudinal Survey of Women and Families. Satisfaction with husbands' participation in housework was classified as satisfactory, less satisfactory, and dissatisfactory. A generalized estimating equations model was used to examine the association. Those who were dissatisfied with their husbands' participation in housework were 2.65 times more likely to think about suicide than those who were satisfied. Subgroup analysis showed that women with an egalitarian gender ideology or low job dissatisfaction were more likely to think about suicide when they were dissatisfied with their husbands' participation in housework. In conclusion, married working women who were dissatisfied with their husbands' participation in housework are more likely to think about suicide than those who are satisfied. Therefore, fostering an environment of fair distribution of housework is necessary for alleviating their stress from the dual burden of work and family. (Copyright © 2018 Elsevier B.V. All rights reserved.)
Keywords: 2000 à aujourd'hui; 2010-2019; asie; charge mentale; corée du sud; discipline; maternité; médecine; projet charge mentale; psychiatrie; périodes historiques; régions géographiques; santé; santé mentale des femmes mariées; suicide; thématiques

Accidental teachers: The journeys of six japanese women from the corporate workplace into english language teaching - Yoshihara, Reiko (Journal of Language, Identity, and Education, 2018)
This study explores the processual identity formation of six Japanese women who gave up a job, turned to higher education, and became university EFL teachers in Japan. My research questions include: (1) How did they change their careers and become university EFL teachers? (2) Since they entered the university EFL teaching profession, how have they felt about their own gender? and (3) How did their working experience influence their EFL teaching? Drawing on a poststructural feminist theory of identity, I examine their nonlinear, changing and contested teacher identities in social, economic and political contexts. Their stories help us understand the complex relations between individuals and the gendered social world and hidden issues involving self-conflict, a sense of unfairness, the burden of gender-differentiated expectation, and emotional strain. I also draw attention to the use of their former identities as a component of their pedagogy, which leads to feminist teaching.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asie; conciliation famille-travail; famille; femmes* universitaires; japon; post-structuralisme; postmodernisme; projet charge mentale; périodes historiques; régions géographiques; thématiques; travail

Luttes féministes autour de la morale sexuelle - Escoda M.R.I.; Praz A.-F.; Lepinard E. (Nouvelles Questions Feministes, 2016)
Keywords: 1900-1999; 2000 à aujourd'hui; 2010-2019; amitié; approches et analyses; asie; cours; discipline; europe; hétérosexisme; phi2030; philosophie; point de vue situé; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques

Infiltrated Intimacies: The Case of Palestinian Returnees - Shalhoub-Kevorkian, Nadera (Feminist Studies, 2016)
This essay examines Palestinian women’s struggles following the 1948 Nakba, when many challenged their uprooting by attempting to return back to their homes and land. Analyzing women’s narratives recounting their experiences from 1948 to 1953 within the context of the settler-colonial regime of control, the essay reveals Israel’s criminalization of the return of Palestinian refugees as acts of “infiltration,” and the unspoken gendered history of trauma that infiltrates the intimate space of women’s families, bodies, and lives. By sharing women’s voices and their embodied memories about childbirth, menstruation, intimate family life, their homes, and domestic life, the article works to provide gender analyses of the political work of suffering, to demonstrate how women were uniquely targeted and affected by such criminalization. Unmasking the political history of trauma and suffering and borrowing meanings from women cast out as illegal by the Israeli state, positions women returnees as frontliners against the political illegality and criminalization of settler colonialism.
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; asie; cours; discipline; droit; féminisme arabe; féminisme décolonial; féminisme islamique; histoire et politique; israël; nakba; palestine; pol4212; premier cycle; périodes historiques; régions géographiques; science politique et droit; système colonial; systèmes d'oppressions; thématiques; violences

Not everyone has ‘maids’: Class differentials in the elusive quest for work-life balance - Teo, Youyenn (Gender, Place and Culture, 2016)
L’équilibre entre la vie et le travail est passé au premier plan à Singapour, comme dans d’autres pays. Les débats se concentrent sur les charges épargnées entre les générations. Menos atención se ha prestado a cómo influyen los asuntos de clase en el resultado para las mujeres. Dans cet article, il est dit que le régime de travail et de soins à Singapour génère des conséquences désagréables entre les femmes dans leur classe. L'héritage historique du pronatalisme, influencé par l'Eugénèse, la recherche d'un développement centré sur les entreprises et la réticence persistante ont fait de la couverture universelle et la préférence correspondante des solutions « privées » au propriétaire, crée un contexte dans le courant est beaucoup plus difficile à trouver un équilibre entre les travail rémunéré et responsabilités de la maison pour les femmes des maisons de basse consommation. L'individualisation et la commercialisation des nécessités de la maison, à Singapour et dans d'autres endroits en général, tiennent compte des circonstances, des nécessités et du bien-être des femmes dans une situation de classe inférieure et socava la valeur de la maison et le travail du personnel.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asie; capitalisme; conciliation famille-travail; famille; pauvreté des femmes; politiques néolibérales; projet charge mentale; périodes historiques; régions géographiques; singapour; systèmes d'oppressions; thématiques; travail; travail invisible

CIRFF 2015 - Conférence publique: «Race, colonialité & politique» avec Paola Bacchetta (2015)
Conférence de Paola Bacchetta, Université de Californie à Berkeley à la conférence publique «Race, colonialité et politique» organisée en collaboration avec l’Institut Simone-De Beauvoir au Congrès CIRFF2015, mercredi 26 août 2015, UQAM. 7e Congrès international des recherches féministes dans la francophonie (CIRFF2015) http://cirff2015.uqam.ca/ 24 au 28 août 2015, Université du Québec à Montréal.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; antiracisme; approches et analyses; asie; autochtones; décolonialisme; féminisme décolonial; genre; identités LGBTQIA2+; inde; politique; périodes historiques; queer; québec; ressource en ligne; régions géographiques; système colonial; systèmes d'oppressions; thématiques

Visual representation of gender in flood coverage of Pakistani print media - Ali, Zarqa S. (Weather and Climate Extremes, 2014)
This paper studies gender representation in the visual coverage of the 2010 floods in Pakistan. The data were collected from flood visuals published in the most circulated mainstream English newspapers in Pakistan, Dawn and The News. This study analyses how gender has been framed in the flood visuals. It is argued that visual representation of gender reinforces the gender stereotypes and cultural norms of Pakistani society. The gender-oriented flood coverage in both newspapers frequently seemed to take a reductionist approach while confining the representation of women to gender, and gender-specific roles. Though the gender-sensitive coverage displayed has been typical, showing women as helpless victims of flood, it has aroused sentiments of sympathy among readers and donors, inspiring them to give immediate moral and material help to the affected people. This agenda set by media might be to exploit the politics of sympathy but it has the effect of endorsing gender stereotypes.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asie; cinéma; communication; discipline; environnement; inondations; médias; pakistan; patriarcat; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; stéréotypes de genre; systèmes d'oppressions; thématiques

Choisir le sexe de son enfant ? Nouvelles techniques de procréation assistée en Palestine - Memmi, Sarah; Loû, Annabel Desgrées du (Cahiers du Genre, 2014)
Dans la société palestinienne, avoir un garçon dans sa descendance est un enjeu social majeur, qui dans un contexte de réduction de la fécondité, peut conduire à vouloir choisir le sexe de son enfant. Aujourd’hui, des techniques de sélection sexuelle prénatales performantes sont disponibles et ne font l’objet d’aucune couverture légale. Cet article propose d’analyser les attitudes des Palestiniennes vis-à-vis de la sélection sexuelle, lieu d’une régulation informelle au croisement du religieux, de la pression sociale et des positions personnelles des médecins. Elle crée aussi de nouveaux enjeux dans l’espace israélo-palestinien ; la réglementation et l’accès à ces pratiques sont très différents entre Israël et la Palestine.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; asie; corps; corps des femmes; cours; discipline; justice reproductive; maternité; palestine; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques; travail; travail reproductif

Les monologues voilés - Roosen, Adelheid; Germain, Greg; Drissi, Jamila (Axe sud, 2010)
Véritable blockbuster, Les Monologues Voilés ont rencontré un succès phénoménal dès la création au Théâtre de Poche de Bruxelles. Depuis, le spectacle a été joué plus de 180 fois - à guichets fermés - en Belgique et à Paris.Le spectacle nous propose 12 monologues d'une exceptionnelle intensité, drôles, poétiques, émouvants nous offrant le rare privilège d'entrer dans l'intimité de femmes musulmanes, sans fausse pudibonderie ni voyeurisme. [source jaquette].
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; afrique; approches et analyses; arabie saoudite; arts; asie; corps; cours; discipline; europe; féminisme islamique; irak; maroc; militance; pakistan; pays-bas; premier cycle; pédagogie; périodes historiques; régions géographiques; sex2283; somalie; thématiques; théâtre; turquie; égypte